2014
DOI: 10.4081/ija.2014.615
|View full text |Cite
|
Sign up to set email alerts
|

The shikimic acid: an important metabolite for the Aglianico del Vulture wines

Abstract: Shikimic acid is a precursor for the biosynthesis of aromatic amino acids and flavonoids (anthocyanins, tannins and flavonols). In the pharmaceutical industry, it is obtained by extraction of star anise from China, and at a yield of 3-7% it is used for the production of antiviral drug, e.g. oseltamivir. Unlike flavonoids which are only present in the grape skins, shikimic acid is present in the juice together with hydroxycinnamil tartaric acids (caffeic, ferulic and p-coumaric acid). Therefore, their content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Tamborra, Paradiso, et al. (2014), during the ripening kinetics, showed a concentration drop of (+)‐catechin (from 327.6 unripe grape to 123.8 mg/Kg at vintage) and a fallen for (−)‐epicatechin (from 212.0 to 86.0 mg/kg at vintage). On the contrary, its decrease in WS treatment (2023 harvest) may be related to moderate stress and therefore to the subsequent increase in anthocyanins probably because of the upregulation of genes encoding VvMybA1, dihydroflavonol‐4‐reductas, UDP‐glucose flavonoid 3‐O‐glucosyltransferase and leucoanthocyanidin dioxygenase (Berdeja et al., 2015; Castellarin et al., 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Tamborra, Paradiso, et al. (2014), during the ripening kinetics, showed a concentration drop of (+)‐catechin (from 327.6 unripe grape to 123.8 mg/Kg at vintage) and a fallen for (−)‐epicatechin (from 212.0 to 86.0 mg/kg at vintage). On the contrary, its decrease in WS treatment (2023 harvest) may be related to moderate stress and therefore to the subsequent increase in anthocyanins probably because of the upregulation of genes encoding VvMybA1, dihydroflavonol‐4‐reductas, UDP‐glucose flavonoid 3‐O‐glucosyltransferase and leucoanthocyanidin dioxygenase (Berdeja et al., 2015; Castellarin et al., 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Interesting to explain is the trend of shikimic acid (precursor for the biosynthesis of l ‐phenylalanine, l ‐tyrosine and flavonoids) (Tamborra, Bolettieri, et al., 2014) during the 2 years. Although it is indicated that in conditions of water stress its content is down‐regulated (Correia et al., 2018), the greater concentration of the latter in the WS treatment can be explained from the perspective of the immature stage of the grapes.…”
Section: Discussionmentioning
confidence: 99%
“…Tuttavia, molto diversi sono i contenuti tra le diverse tesi, con il valore finale della tesi con incisione anulare del tronco quattro volte più elevato del teste. Di tale variabilità occorre tener conto quando si intenda utilizzare il contenuto di acido scichimico quale marker varietale [11].…”
Section: Risultati E Discussioniunclassified
“…Il ruolo dell'Italia nel contesto mondiale di produzione di uva da tavolaè significativo essendo il quinto produttore al mondo. Nella produzione di uva da tavola gli aspetti carpometrici legati alla dimensione della bacca e del grappolo richiedono una serie di interventi in vigneto in grado di massimizzare tali parametri [1-6] Nella ricerca sono state poste a confronto diverse tecniche quali l'incisione anulare del tronco, l'incisione anulare dei capi a frutto, l'irrorazione di acido gibberellico sui grappoli (due interventi a 40 ppm), valutando alla raccolta sia le dimensioni della bacca che ladotazione dei terpeni, responsabili del caratteristico aroma della varietà Italia [7][8][9][10][11]. L'incisione anulare, cheè stata effettuata in post-allegagione, rientra nella viticoltura da tavola tra le tecniche di potatura verde e consiste nell'incidere e rimuovere un anello di corteccia dal tronco o dal capo a frutto, determinando un interruzione del movimento del flusso floematico [12-15] I risultati della tecnica sono legati all'epoca di esecuzione, con incrementi di allegagione nel caso di interventi in fioritura, mentre in fase di invaiatura sono segnalati incrementi dell'accumulo glucidico con evidente anticipo dell'epoca di raccolta [3] Interventi di incisione e decorticazione anulare hanno determinato l'aumento della disponibilità di carboidrati per i grappoli e miglioramento dello stato idrico delle viti [14].…”
Section: Introduzioneunclassified
“…Shikimic acid is investigated for its beneficial effects and, moreover, it is considered a varietal marker that is usually employed for authenticity and traceability of wines [17,18]. Red wines have a higher content of shikimic acid than white ones [19] and, among red grapes, Aglianico berries have a higher concentration of shikimic acid in comparison to other varieties [20]. The M1, M6, M10, M11, M13, and M14 accessions showed the highest shikimic acid values, ranging from 30.6 to 35.6 mg/L.…”
Section: Resultsmentioning
confidence: 99%